THE EFFECT OF AUDIT COMMITTEE, AUDIT QUALITY AND FIRM SIZE ON THE INTEGRITY OF FINANCIAL STATEMENTS - Trisandi Eka Putri; Leli Rahmawati Setiawan (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2023)
The purpose of this study was to determine the effect of audit committee, audit quality, firm size on the integrity of financial statements in real estate investment trust listed on the Malaysia stock exchange. The are have 4 independent variables in this study including, audit committee measured using number of audit committee, audit quality measured using variable dummy, and firm size measured using SIZE. While the dependent variable of this research is integrity of financial statements with CON . This study uses data form the financial statements of 18 companies for 4 years form 2018-2021 using purposive sampling technique. The data analysis technique used in this study was multiple regression analysis with the help of the SPSS application. The results of this tudy indicate that the variables of audit committee has no effect on the integrity of the financial statements, while audit quality and firm size have negative effect on the integrity of the financial statements.